Revitalizing Waqf Institutions: A Sustainable Solution for Vocational Education and Out-of-School Children in Northern Nigeria - Sani, Shafi’u Mahmud; Muhammad, Adamu Abubakar; Amare, ISA Abubakar Dutsin-; Muhammad, Zuwaira Jibril (Yayasan Abdurrauf Cendekia Nusantara, 2025)
In Northern Nigeria, the growing number of out-of-school children and the difficulties associated with vocational education provide a serious obstacle to sustainable development. Socioeconomic disparities, a lack of adequate government financing, and ineffective institutional frameworks are the main causes of these problems. The potential role of restoring waqf (Islamic endowment) organizations as a long-term solution to these issues is examined in this research. In Islamic nations, waqf organizations have traditionally played a significant role in funding social welfare, healthcare, and education. Waqf can offer the infrastructure and resources required to support vocational education and reintegrate out-of-school youth into the educational ecosystem by utilizing their innate values of generosity and community empowerment. The study emphasizes the working mechanisms of waqf and its applicability to contemporary socio-economic requirements by combining qualitative and quantitative research methodologies. It looks at effective waqf models in other Islamic countries and assesses how well they work in Northern Nigeria. It also provides a strategic framework for waqf institution revitalization, which includes capacity building, legal reforms, and waqf integration with current public and commercial programs. The results show that a well-designed waqf system may sustainably fund educational facilities, scholarships, and vocational training centers, lowering poverty and promoting economic independence among underserved areas. The study comes to the conclusion that government agencies, religious institutions, and civil society organizations must work together to revive waqf institutions for addressing the existing challenges in the vocational education, and out-of-school children circle in northern Nigeria. By addressing the dual challenge of vocational education and out-of-school children, waqf institutions can play a transformative role in shaping a more equitable and prosperous Northern Nigeria. [Di Nigeria Utara, meningkatnya jumlah anak yang tidak bersekolah serta berbagai kendala dalam pendidikan kejuruan menjadi hambatan serius bagi pembangunan berkelanjutan. Ketimpangan sosial-ekonomi, kurangnya pendanaan pemerintah yang memadai, serta kelemahan dalam kerangka kelembagaan merupakan faktor utama yang menyebabkan permasalahan ini. Penelitian ini mengkaji potensi revitalisasi lembaga wakaf sebagai solusi jangka panjang terhadap permasalahan tersebut. Dalam sejarah negara-negara Islam, lembaga wakaf telah memainkan peran penting dalam pembiayaan kesejahteraan sosial, layanan kesehatan, dan pendidikan. Dengan mengedepankan nilai-nilai kedermawanan dan pemberdayaan komunitas, wakaf dapat menyediakan infrastruktur dan sumber daya yang diperlukan untuk mendukung pendidikan kejuruan serta mengintegrasikan kembali anak-anak yang tidak bersekolah ke dalam sistem pendidikan. Penelitian ini menggunakan metode kualitatif dan kuantitatif untuk menganalisis mekanisme kerja wakaf dan relevansinya terhadap kebutuhan sosial-ekonomi kontemporer. Studi ini juga menelaah model wakaf yang berhasil diterapkan di negara-negara Islam lainnya serta mengevaluasi efektivitasnya di Nigeria Utara. Selain itu, penelitian ini mengusulkan kerangka strategis untuk revitalisasi lembaga wakaf, yang mencakup peningkatan kapasitas, reformasi hukum, dan integrasi wakaf dengan program publik serta sektor swasta yang telah ada. Hasil penelitian menunjukkan bahwa sistem wakaf yang dirancang dengan baik dapat secara berkelanjutan membiayai fasilitas pendidikan, beasiswa, dan pusat pelatihan kejuruan, sehingga berkontribusi dalam pengurangan kemiskinan serta peningkatan kemandirian ekonomi bagi kelompok masyarakat yang kurang beruntung. Kesimpulan penelitian ini menegaskan bahwa kolaborasi antara lembaga pemerintah, institusi keagamaan, dan organisasi masyarakat sipil sangat diperlukan dalam merevitalisasi lembaga wakaf guna mengatasi permasalahan pendidikan kejuruan dan anak-anak yang tidak bersekolah di Nigeria Utara. Dengan mengatasi tantangan ganda ini, lembaga wakaf dapat berperan secara transformatif dalam menciptakan masyarakat Nigeria Utara yang lebih adil dan sejahtera. Kata kunci: Lembaga Wakaf, Pendidikan Kejuruan, Anak Tidak Bersekolah, Nigeria Utara, Pembangunan Berkelanjutan]